2020
DOI: 10.1111/ans.16079
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of early ileostomy reversal: a systematic review and meta‐analysis

Abstract: Background Recent evidence supports the safety of early reversal of a temporary stoma, within 14 days of construction. The aim of this systematic review and meta‐analysis was to evaluate the post‐operative morbidity and overall feasibility of early stoma reversal. Methods Medline and Cochrane databases were searched for studies up to June 2019 that investigated the outcomes of early stoma reversal (EC, defined as closure ≤14 days from the index operation) versus late stoma reversal (LC, ≥8 weeks from the index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Ng et al [ 217 ], in their pooled analysis of 667 patients from nine studies, confirmed the safety of EC, with an associated reduction in stoma-related complications (8.4% vs. 33.4%, RD = − 0.28, P = 0.001) despite a higher wound infection rate (18.6% vs. 7.1%, RD = 0.10, P = 0.047). The meta-analysis showed no significant difference in the postoperative morbidity rate, anastomotic leak rate, rates of small bowel obstruction, bleeding, and ileus between EC and LC.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Ng et al [ 217 ], in their pooled analysis of 667 patients from nine studies, confirmed the safety of EC, with an associated reduction in stoma-related complications (8.4% vs. 33.4%, RD = − 0.28, P = 0.001) despite a higher wound infection rate (18.6% vs. 7.1%, RD = 0.10, P = 0.047). The meta-analysis showed no significant difference in the postoperative morbidity rate, anastomotic leak rate, rates of small bowel obstruction, bleeding, and ileus between EC and LC.…”
Section: Resultsmentioning
confidence: 89%
“…To improve QoL, early stoma closure within 2 weeks from the index operation has been proposed. Six randomized controlled trials [ 204 , 210 214 ] published over the past 10 years, and four systematic reviews with meta-analysis published over the past 2 years [ 202 , 215 – 217 ] were evaluated by the meta-analysis team.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with a high risk of renal function damage who require a temporary diverting stoma, more rigorous monitoring of fluids, electrolytes, and renal function is needed. Moreover, other preventative methods such as colostomy instead of ileostomy to reduce water and electrolyte loss (30), as well as shortening the time to stoma closure, might help to decrease the occurrence of renal function impairment in high-risk patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent meta-analyses have suggested that early ileostomy closure is effective and safe in selected patients [21][22][23][24]. However, others reported that early closure increased the rate of post-operative complications [25].…”
Section: Introductionmentioning
confidence: 99%